2010
DOI: 10.1111/j.1550-7408.2010.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirotontonia taiwanica n. sp. (Ciliophora: Oligotrichida) from the Coastal Waters of Northeastern Taiwan: Morphology and Nuclear Small Subunit rDNA Sequence

Abstract: The marine oligotrichous ciliate Spirotontonia taiwanica n. sp. isolated from the coastal waters of northeastern Taiwan is reported, using live observation, protargol preparations and molecular data. The new species differs from the most similar, known congener Spirotontonia turbinata in the following features: (1) lower number of buccal membranelles (11-13 vs. 13-17); (2) higher number of whorls of girdle kinety (2.5 vs. 1.5); (3) lower number of macronuclear nodules (20-31 vs. 28-40); (4) larger cell size (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The South China Sea is located in the northern tropics and possesses a range of habitats along its Chinese coastline, including mangrove wetlands, estuaries, and bays, all of which contribute to a high diversity of planktonic ciliated protozoa (Liu et al, 2009(Liu et al, , 2010Tsai, Chen, & Chiang, 2010;Tsai, Xu, Chung, & Chiang, 2008;Wang et al, 2014). Recent studies on the diversity of ciliates from this area have observed »20 oligotrich species, including a new family and a new genus Liu, Yi, Lin, & Al-Rasheid, 2011a;Liu, Yi, Lin, Warren, & Song, 2012;Liu et al, 2011bLiu et al, , 2015aLiu et al, , 2015bSong et al, 2013Song et al, , 2015Zhang, Zhang, & Xiao, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…The South China Sea is located in the northern tropics and possesses a range of habitats along its Chinese coastline, including mangrove wetlands, estuaries, and bays, all of which contribute to a high diversity of planktonic ciliated protozoa (Liu et al, 2009(Liu et al, , 2010Tsai, Chen, & Chiang, 2010;Tsai, Xu, Chung, & Chiang, 2008;Wang et al, 2014). Recent studies on the diversity of ciliates from this area have observed »20 oligotrich species, including a new family and a new genus Liu, Yi, Lin, & Al-Rasheid, 2011a;Liu, Yi, Lin, Warren, & Song, 2012;Liu et al, 2011bLiu et al, , 2015aLiu et al, , 2015bSong et al, 2013Song et al, , 2015Zhang, Zhang, & Xiao, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…are one of the most common groups of planktonic ciliates, inhabiting in both marine and fresh waters (e.g., Agatha 2011;Gao et al 2009;Foissner and Wilbert 1979;Kim et al 2010;Liu et al 2009Liu et al , 2011aMcManus et al 2010;Tsai et al 2010;Zhang et al 2010). Considering the pathway of energy and materials, they are important elements of the planktonic food web (Choi et al 1992;Dolan 1991;Jiang et al 2011a,b;Pierce and Turner 1992, 1994.…”
Section: Introductionmentioning
confidence: 99%
“…DNA extraction was carried out according to Tsai et al. (, ). A polymerase chain reaction (PCR) was performed in a buffer containing 3 mM MgCl 2 , 0.25 mM dNTP, 10 −3 mM forward (5′‐AAC CTG GTT GAT CCT GCC AGT‐3′) and reverse (5′‐TCC TTC TGC AGG TTC ACC TAC‐3′) primers (Medlin et al.…”
Section: Methodsmentioning
confidence: 99%